Dynamic modelling of N2O emissions from a full‐scale granular sludge partial nitritation‐anammox reactor. Issue 6 (22nd February 2022) - Wan, Xinyu; Volcke, Eveline I.P.
Abstract: Partial nitration‐anammox is a resource‐efficient pathway for nitrogen removal from wastewater. However, the advantages of this nitrogen removal technology may be counter‐acted by the emission of N2 O, a potent greenhouse gas. In this study, mathematical modelling was applied to analyse N2 O formation and emission dynamics and to develop N2 O mitigation strategies for a one‐stage partial nitritation‐anammox granular sludge reactor. Dynamic model calibration for such a full‐scale reactor was performed, applying a one‐dimensional biofilm model and including several N2 O formation pathways. Simultaneous calibration of liquid phase concentrations and N2 O emissions leads to improved model fit compared to their consecutive calibration. The model could quantitatively predict the average N2 O emissions and qualitatively characterize the N2 O dynamics, adjusting only seven parameter values. The model was validated with N2 O data from an independent data set at different aeration conditions. Nitrifier nitrification was identified as the dominating N2 O formation pathway. Off‐gas recirculation as a potential N2 O emission reduction strategy was tested by simulation and showed indeed some improvement, be it at the cost of higher aeration energy consumption. Abstract : Dynamic N2 O modeling full‐scale partical nitritation‐anammox.